Pedagogía teatral. una propuesta teórico-metodológica crítica - Vazquez Lomelí, Carlos Manuel (CALLE14: revista de investigación en el campo del arte, 2011)
The Theatrical Critic Pedagogy (TCP), a theoretical methodological approach for the formation of professional actors, undertakes positions that problematizes XXth century’s theatrical pedagogy, and conceptualizes terms and notions from disciplines that contribute with inputs to the teaching and learning process of the actor, from a critical and reflexive perspective. The pedagogical TCP intention is to put into context the actor’s dramatic action in the scene as a social and cultural action: on one hand, to favor the critical knowledge of the subject-actor’s social and cultural environment by way of empowerment, and at the same time to offer the subject’s resistance to the dominant official representations and speeches of institutions that hold the social power, expressed at the level of ideological, cultural and political speeches. The theatrical communication between the spectator and a critical and reflexive actor formed with the TCP is conceived as a scene-vision communicative process.